Probing into a peaceful bay from the concentration of capital in Saul Bellow's Dangling Man (IIUC Studies, 2026)
This paper explores a peaceful bay in capitalist society as presented in Saul Bellow's Dangling Man through the concept of Emile Durkheim's 'Collective Conscience,' 'Social Integration,' and 'Organic Solidarity'. The interaction of these concepts is not out of relevance, mostly because Durkheim provides a facet of society, a living organism, where these concepts show a connectivity among them; the collective consciousness of having morals, attitudes and beliefs of a society activates the social integration which leads to organic solidarity of those who live with differing values. Moreover, Dangling Man delineates a man, Joseph, who finds difficulty in integrating himself into his capitalist society for its concentration of capital. He faces a conflict between his reality and his individuality which deters him from coping with society. As he undergoes complex personal matters, his wish to liberate himself from the entanglements of his community directs him to search for a place to which he attaches himself. By showing Joseph’s life under the strain of the concentration of capital, the paper probes whether Joseph finds a peaceful bay in his life to rejuvenate himself, which can be analyzed from diverse viewpoints. Thus, the study exposes how Joseph's attempt to regenerate himself fits into the ideas of Durkheim.IIUC Studies, Vol.-21, Issue-1, Dec. 2024, pp. 91-104